Study the effect of some processing methods on the viability of sarcocystis cysts by using vital staining techniques - Arafa, Mohsen I.; Nagieb, Basem; Tawfik, Mohamed. S.; Abd-El-Malek, Ashraf M.; Heneter, Asmaa M. (Journal of Advanced Veterinary Research, 2025)
Sarcocystis spp. is one of the most prevalent and pervasive livestock protozoan parasites. The overall Sarcocystis infection rate among the examined 80 buffaloes in the Assiut Governorate was 70%. Both macroscopic sarcocysts (3.75%) and microscopic sarcocysts (67.5%) differed significantly. The esophagus was the only affected organ exhibiting macroscopic sarcocysts. Besides, microscopic cysts were most prevalent in the esophagus (45%), skeletal muscles (42%) then followed by the diaphragm (36%), heart (33%), masseter muscle (27%) and tongue (25%) without statistical influence. Assessment of parasite vitality is essential in order to demonstrate the success of inactivation procedures, In terms of vital stains two techniques trypan blue staining Acridine orange staining were applied in our study. Different processing and storage techniques were assessed in this study as control measures for sarcocystosis in esophageal tissue. The viability of sarcocystis cysts after 24 hrs. of chilling at 4oC was unaffected, but the survival rate dropped to 48.5% after 48 hrs. of storage with a very high significant difference. Storing esophageal tissue at -18oC for 48 hrs. completely ruined the viability of sarcocystis cysts, whereas at 24 hrs., survival rate was 40.4%, exhibiting a highly significant difference. Microwave treatments employed for (30 sec, 1, 2 and 3 minutes) resulted in 100% mortality of the bradyzoites however for 15 sec. the survival rate was 74.4%, exhibiting a highly significant difference. Treatment I (2% NaCl, 2% pot. Lactate) and Treatment II (2% NaCl, 3% pot. Lactate) showed 40.7% and 21.7% survival rate for sarcocystis cysts, respectively.